Atopic dermatitis-associated genetic variants regulate LOC100294145 expression implicating interleukin-27 production and type 1 interferon signaling - Teo, Wei Yi; Lim, Eliza Yi Ying; Sio, Yang Yie; Say, Yee How*; Kavita, Reginald *; Chew, Fook Tim (Elsevier, 2024)
Background Atopic dermatitis (AD) is a complex inflammatory disease with a strong genetic component. A singular approach of genome wide association studies (GWAS) can identify AD-associated genetic variants, but is unable to explain their functional relevance in AD. This study aims to characterize AD-associated genetic variants and elucidate the mechanisms leading to AD through a multi-omics approach.